The Effect Of Rewards And Sports Facilities On The Performance Of Wushu Athletes (A Study Of Wushu Taolu Athletes At The Youth And Sports Office Of Ogan Komering Ulu Regency) - Rita Sunarti; Munajat; Mardiah Kenamon (Institute for Law and Economics Studies, 2026)
This study focuses on examining two key factors believed to have a significant influence on the performance of wushu taolu athletes: the variables under investigation, namely rewards and sports facilities at the OKU Regency Youth and Sports Office. The research method employed is a quantitative descriptive approach; this study utilises saturation sampling or a census, whereby the entire population of 40 athletes was selected as the research sample. The results of the study show that the calculation of the variable. Reward (X1) against Performance (Y) yielded a significance value of 0.009 < 0.05. Sports Facilities (X2) on Performance (Y) yielded a significance value of 0.014 < 0.05. Meanwhile, the simultaneous analysis yielded a significance value of 0.003, which is smaller than α = 0.05 (0.003 < 0.05). The R-squared value is 0.264. It can therefore be concluded that the independent variables Reward (X1) and Sports Facilities (X2) have a partial and simultaneous effect on performance (Y) of 26.4%, whilst the remainder is attributable to variables outside the scope of this study.